Spandex fabric basic characteristic flexible stretchable zinc ion battery and preparation method thereof

By dynamically stretching electroplating of galvanizing and solidifying active substances on a spandex fabric substrate, combined with in-situ crosslinking polymer electrolytes, a flexible stretchable zinc ion battery that can maintain electrochemical performance under large tensile deformation was prepared, solving the problem of unstable performance of existing batteries under complex deformation.

CN119852602APending Publication Date: 2025-04-18HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510023088.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing flexible zinc ion batteries cannot effectively maintain electrochemical performance under complex deformation such as large stretching, and the electrode materials are prone to rupture and fall off under strain, which limits their application in the wearable field.

Method used

The stretchable battery anode and cathode are prepared by dynamic stretching electroplating of galvanized and dynamic stretching of ultraviolet rays to solidify active substances, and the polymer electrolytes are crosslinked in situ on the electrodes to form a flexible stretchable zinc ion battery with a sandwich structure.

Benefits of technology

The stable electrochemical performance of the battery under 100% maximum tensile strain is achieved, and the phenomenon of cracking and layering of the battery during deformation is avoided, and it has good bendable, curling, twisting and tensile deformation capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852602A_ABST
    Figure CN119852602A_ABST
Patent Text Reader

Abstract

The invention discloses a spandex fabric basic characteristic flexible stretchable zinc ion battery and a preparation method thereof. According to the method, a spandex fabric-based zinc anode and a spandex fabric-based single-walled carbon nanotube cathode are prepared by dynamically stretching electrogalvanizing and dynamically stretching ultraviolet irradiation solidification active substance printing ink on a spandex fabric respectively, a polymer electrolyte membrane is cross-linked on an electrode and separates the cathode from the anode, and then edge sealing is carried out; the flexible stretchable zinc ion battery with the sandwich structure is obtained. The flexible and stretchable zinc ion battery not only can charge and discharge, but also has good bendable, curled, twisted and stretchable characteristics, can be stretched to 100%, keeps stable charge and discharge performance after different tensile deformations, and has a very good application prospect in the field of wearable devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of intelligent energy storage devices, and in particular to a spandex fabric-based flexible stretchable zinc ion battery and a preparation method thereof. Background Art

[0002] In recent years, flexible and stretchable electronic devices have received extensive attention. They can be applied to high-tech fields such as smart wearables, robots, and artificial organs, and are considered to be one of the most promising research directions. Flexible and stretchable supercapacitors, lithium-ion batteries, lithium-sulfur batteries, alkaline batteries and other energy storage devices have been developed. Zinc-ion batteries have a high theoretical capacity (5855mAh cm -3 or 820mAh g -1 ), low cost, safety, environmental protection and other advantages have attracted widespread attention. At present, some scientific research on the preparation of flexible zinc-ion batteries has made certain progress. Flexible zinc-ion batteries are expected to provide energy for some wearable and portable electronic devices.

[0003] Generally speaking, flexible zinc-ion batteries are composed of a zinc metal anode, a polymer electrolyte, and a flexible cathode (usually a carbon cloth material). One-dimensional linear zinc-ion batteries and two-dimensional sandwich-structured zinc-ion batteries have been developed. Affected by the rigidity and non-deformability of zinc and carbon cloth materials, most of these developed zinc-ion batteries can only undergo simple bending deformation or small tensile deformation, and cannot undergo complex deformations such as large stretching. In addition, conventional flexible stretchable zinc-ion batteries are made by preparing active material powder into electronic ink and coating it on a stretchable substrate, or by using a spatial structure design to give the rigid conductive material a certain degree of buffering to prevent the material itself from directly undergoing deformation. However, such electrode materials may break and fall off under strain. All of the above have severely restricted the application of flexible stretchable zinc-ion batteries in the wearable field, so it is of great significance to develop a new flexible stretchable zinc-ion battery and preparation method. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a flexible stretchable zinc ion battery based on spandex fabric and a preparation method thereof. Due to the unique weaving structure of spandex fabric, the present invention deposits active substances on the spandex fabric, which can ensure high tensile properties and ensure that the active substances will not break or fall off under tensile deformation. In this way, the tensile properties of the electrode and the polymer electrolyte are comparable and matched, which can avoid the assembled battery from cracking and delaminating and being destroyed when deformed. The prepared battery can withstand a maximum tensile strain of 100% and also exhibits stable electrochemical properties under different tensile conditions.

[0005] In a first aspect, the present invention provides a flexible and stretchable zinc ion battery based on spandex fabric, which is realized by the following technical scheme.

[0006] A spandex fabric-based flexible stretchable zinc ion battery, comprising a stretchable electrode and a stretchable gel electrolyte film; the stretchable electrode comprises a spandex fabric-based anode and a spandex fabric-based cathode, and the stretchable gel electrolyte film is arranged between the spandex fabric-based anode and the spandex fabric-based cathode;

[0007] The spandex fabric-based anode is a spandex fabric-based galvanized electrode, the spandex fabric-based galvanized electrode comprises a copper-plated layer and a galvanized layer arranged outside the copper-plated layer, and the copper-plated layer is a copper-plated fabric;

[0008] The spandex fabric-based cathode is a spandex fabric-based active substance ink electrode, which includes a single-walled carbon nanotube layer and an active substance ink layer outside the single-walled carbon nanotube layer; the single-walled carbon nanotube layer is a fabric sprayed with a single-walled carbon nanotube dispersion, and the active substance ink layer is a dynamically stretched ultraviolet irradiation solidified active substance ink.

[0009] The stretchable electrolyte film is selected from one or more of polyvinyl alcohol hydrogel, polyacrylamide hydrogel, spandex fabric-based polyvinyl alcohol hydrogel, and spandex fabric-based polyacrylamide hydrogel.

[0010] By adopting the above technical scheme, the existing battery negative electrode that is electrogalvanized is often used in zinc ion batteries that cannot be stretched to prevent the formation of zinc electrode dendrites. The zinc anode prepared by the method of dynamic stretching electrogalvanizing on a spandex fabric in the present application not only ensures the tensile properties of the electrode, allowing the electrode to be stretched by more than 100%, but also inhibits the formation of zinc electrode dendrites. In addition, the present invention prepares a stretchable battery cathode on a spandex fabric by a method of dynamic stretching-ultraviolet irradiation coagulation of active substances, and the prepared electrode can also be stretched by more than 100%. The manufactured battery can be stretched by 100% and has good electrochemical properties.

[0011] Furthermore, the method for preparing the copper plating layer comprises the following steps:

[0012] A1. Cut the spandex fabric into small pieces and perform surface modification treatment;

[0013] A2. Immerse the treated spandex fabric in the degreasing solution for 10-60 minutes, wash it with water, and then pre-stretch the spandex fabric by 120%. 2 Vacuum immersion in hydrochloric acid solution for 10-60 minutes, then take it out and immerse it in PdCl 2 Vacuum impregnation in a hydrochloric acid solution for 10-60 minutes to obtain a surface-activated spandex fabric;

[0014] A3. Soaking the surface activated spandex fabric in a chemical copper plating solution to deposit metallic copper on the surface to form a copper plating layer, thereby obtaining a copper-plated fabric.

[0015] Furthermore, in step A1, the spandex fabric area is 6-9cm 2 Preferably, the size of the spandex fabric is 2.5 cm×3 cm, and the surface modification treatment is carried out by an air plasma cleaning machine for 4-10 min; in step A2, SnCl 2 The concentration of hydrochloric acid solution is 30-100mM, PdCl 2 The concentration of the hydrochloric acid solution is 1-5 mM; in step A3, the soaking temperature is 30-40° C. and the soaking time is 2-8 h.

[0016] Furthermore, the preparation method of the spandex fabric-based galvanized electrode includes the following steps: adopting a dynamic stretching method, using the copper-plated layer as the cathode and the zinc plate as the anode to form a two-electrode electroplating system, electroplating for 10-20 minutes at a voltage of -0.5V to -2V to form a zinc-plated layer, and obtaining a spandex fabric-based galvanized electrode; during the dynamic stretching process, the copper-plated fabric can continuously maintain a stretching and recovery cycle, with each cycle being 1.5-2.5s.

[0017] Furthermore, the method for preparing the single-walled carbon nanotube layer comprises the following steps:

[0018] B1. Prepare a surfactant sodium dodecyl sulfate solution with deionized water, and then add the single-walled carbon nanotube powder into the solution;

[0019] B2, subjecting the above solution to ultrasonic oscillation treatment to obtain a stably dispersed carbon nanotube suspension;

[0020] B3. Take the dry spandex fabric after surface modification and degreasing, pre-stretch it to 120%, spray the carbon nanotube suspension on both sides of the fabric, then release the stretch and dry the fabric, wash the dried fabric several times and dry it to obtain a single-walled carbon nanotube layer.

[0021] Furthermore, in step B1, the concentration of sodium dodecyl sulfate solution is 0.1-0.15 g / L; in step B2, ultrasonic oscillation treatment is carried out by ultrasonic cell crusher, the power is 500-700 W, the ultrasonic time is 30-50 min, and the concentration of the obtained carbon nanotube suspension is 0.05-0.1 g / L; in step B3, surface modification treatment is carried out by air plasma cleaning machine, the treatment time is 3-5 minutes; the drying temperature is 50-70 ° C, and the drying time is 1-3 hours. The single-walled carbon nanotube loading is 2.8 mg cm -2 .

[0022] Furthermore, the method for preparing the active material ink comprises the following steps:

[0023] C1, mixing an aqueous carbon nanotube dispersion and an aqueous graphene dispersion into water, adding methylenebisacrylamide and ammonium persulfate initiator, and performing ultrasonic treatment to make the dispersion uniform;

[0024] C2. Add the active substance to the above solution, sonicate again, add sodium carboxymethyl cellulose, and stir thoroughly until completely dissolved;

[0025] C3. Add acrylamide to the obtained solution, stir, and prepare active material ink.

[0026] Furthermore, in step C1, the carbon nanotube content in the aqueous carbon nanotube dispersion is 10%; and the graphene content in the aqueous graphene dispersion is 50%.

[0027] Furthermore, in step C1, the mass ratio of the aqueous carbon nanotube dispersion to the aqueous graphene dispersion is (0.8-0.9):0.17, the mass ratio of methylenebisacrylamide to the aqueous graphene dispersion is (0.001-0.003):0.85, and the mass ratio of ammonium persulfate to the aqueous graphene dispersion is (0.01-0.03):0.85; in step C2, the active material is a metal oxide, and the metal oxide includes MnO 2 、V 2 O 5 , Fe 3 O 4 , the mass ratio of active substance to aqueous graphene dispersion is (0.4-0.6):0.85, the ultrasonic time is 8-10 minutes, the mass ratio of sodium carboxymethyl cellulose to aqueous graphene dispersion is (0.03-0.05):0.17; in step C3, the mass ratio of acrylamide to aqueous graphene dispersion is (0.1-0.3):0.17, and the stirring time is 1-3 hours. The loading amount of the active substance ink is 53 mg cm -2 .

[0028] Furthermore, the preparation method of the spandex fabric-based active substance ink electrode includes the following steps: stretching the fabric sprayed with the single-walled carbon nanotube dispersion to 100%, uniformly coating the active substance ink on the fabric current collector by a scraper method, and then immediately releasing the stretching; using a dynamic stretching method, exposing the fabric to ultraviolet light for 20-30 minutes to solidify the active substance ink on the single-walled carbon nanotube coated fabric to obtain a spandex fabric-based active substance ink electrode.

[0029] Furthermore, the UV wavelength is 365nm and the power is 5W.

[0030] Furthermore, the polyvinyl alcohol hydrogel adopts PVA / ZnCl 2 / MnCl 2The polyacrylamide hydrogel is prepared by using PAM / ZnSO 4 / MnSO 4 The precursor liquid is prepared.

[0031] By adopting the above technical solution, PVA / ZnCl 2 / MnCl 2 The characteristic of the electrolyte formed by the precursor liquid is good tensile properties, which is conducive to filling between the electrodes. The tensile properties of the electrolyte play an important role in the tensile properties of the stretchable zinc-ion battery, enabling the battery to maintain stable electrochemical properties during tensile deformation. 2 / MnCl 2 The electrolyte formed by the precursor liquid has good flexibility, which enables the electrolyte to be cross-linked in situ on the electrode. By cross-linking the electrolyte in situ on the electrode, the electrolyte fills the surface of the spandex fabric, and sufficient contact between the electrode and the electrolyte is achieved.

[0032] Furthermore, the preparation method of polyvinyl alcohol hydrogel is as follows:

[0033] ZnCl 2 and MnCl 2 Dissolve in acidic water to prepare a gel electrolyte; then add ethylene glycol and graphene oxide dispersion to make the solution uniformly dispersed, then disperse and add PVA to make PVA fully swell, stir the solution in a water bath at 90-95°C for 1-2h, then pour the gel precursor into a mold, freeze-dry overnight to obtain PVA / ZnCl 2 / MnCl 2 Hydrogel film; wherein ZnCl 2 and MnCl 2 The concentration ratio of ZnCl is 9:1-10:1 2 The mass ratio of PVA, ethylene glycol and graphene oxide is (5-6):(3-4):1:1; the pH value of acidic water is 4-6.

[0034] Furthermore, the preparation method of spandex fabric-based polyvinyl alcohol hydrogel is as follows:

[0035] ZnCl 2 and MnCl 2 Dissolve in acidic water to prepare gel electrolyte; then add ethylene glycol and graphene oxide dispersion to make the solution evenly dispersed, then disperse and add PVA to make PVA fully swell, stir the solution in a water bath at 90-95°C for 1-2h, then place the treated spandex fabric in a mold, evenly cast the gel precursor on the spandex fabric, freeze-dry overnight, and obtain spandex fabric-based PVA / ZnCl 2 / MnCl 2Hydrogel film; wherein ZnCl 2 and MnCl 2 The concentration ratio of ZnCl is 9:1-10:1 2 The mass ratio of PVA, ethylene glycol and graphene oxide is (5-6):(3-4):1:1; the pH value of acidic water is 4-6.

[0036] Furthermore, the preparation method of polyacrylamide hydrogel is as follows:

[0037] ZnSO 4 and MnSO 4 Dissolve in deionized water, add acrylamide and stir to dissolve, then add methylenebisacrylamide, ammonium persulfate and tetramethylethylenediamine respectively, stir to dissolve evenly, then pour the gel precursor into the mold, polymerize at 60-80℃ for 30-60 minutes to obtain PAM / ZnSO 4 / MnSO 4 Hydrogel film; wherein ZnSO 4 and MnSO 4 The concentration ratio of ZnSO is 9:1-10:1. 4 The mass ratio of acrylamide, methylenebisacrylamide, ammonium persulfate and tetramethylethylenediamine is (11-12):(3-4):0.0024:0.024:0.028.

[0038] Furthermore, the preparation method of spandex fabric-based polyacrylamide hydrogel is as follows:

[0039] ZnSO 4 and MnSO 4 Dissolve in deionized water, add acrylamide and stir to dissolve, then add methylenebisacrylamide, ammonium persulfate and tetramethylethylenediamine respectively, stir and dissolve evenly, place the treated spandex fabric in a mold, cast the gel precursor evenly on the spandex fabric, polymerize at 60-80℃ for 30-60 minutes, and obtain spandex fabric PAM / ZnSO 4 / MnSO 4 Hydrogel film; wherein ZnSO 4 and MnSO 4 The concentration ratio of ZnSO is 9:1-10:1. 4 The mass ratio of acrylamide, methylenebisacrylamide, ammonium persulfate and tetramethylethylenediamine is (11-12):(3-4):0.0024:0.024:0.028.

[0040] In a second aspect, the present invention provides a method for preparing a flexible and stretchable zinc-ion battery based on spandex fabric, which is achieved through the following technical solutions.

[0041] A method for preparing the above-mentioned spandex fabric basic flexible stretchable zinc ion battery comprises the following steps:

[0042] D1. Paste the spandex fabric-based galvanized electrode on the elastic rubber film or the spandex fabric-based elastic silicone rubber film, and then cure it to obtain a bonded spandex fabric-based galvanized anode-rubber film;

[0043] D2, pasting the spandex fabric-based active substance ink electrode on the elastic rubber film or the spandex fabric-based elastic silicone rubber film, and then curing it to obtain a well-bonded spandex fabric-based active substance ink cathode-rubber film;

[0044] D3. Coat the liquid gel precursor of the stretchable electrolyte film on the spandex fabric-based galvanized anode and the spandex fabric-based active material ink cathode, then stack and assemble the spandex fabric-based galvanized anode and the spandex fabric-based active material ink cathode, and set the stretchable electrolyte film between the two electrodes, and then cure and seal the edges to form a flexible stretchable zinc ion battery with a sandwich structure.

[0045] Furthermore, the elastic rubber film is prepared by mixing Ecoflex-0050 silicone rubber A and B liquids in a weight ratio of 1:1 to form an Ecoflex precursor liquid, pouring the Ecoflex precursor liquid into a mold, and then treating it at 50-80° C. for 1 hour to crosslink and cure it.

[0046] Furthermore, the spandex fabric-based elastic silicone rubber membrane is prepared by mixing Ecoflex-0050 silicone rubber A and B liquids in a weight ratio of 1:1 to form an Ecoflex precursor liquid, pouring the Ecoflex precursor liquid into a mold, and then immersing the treated spandex fabric in the Ecoflex-0050 precursor solution, and then treating it at 50-80° C. for 1 hour to cross-link and cure it.

[0047] This application has the following beneficial effects.

[0048] The present invention uses a spandex fabric-based galvanized electrode and a spandex fabric-based active material electrode as the anode and cathode respectively, and the polymer electrolyte membrane is cross-linked in situ on the electrode to separate the cathode and the anode, and then the edges are sealed to obtain a flexible zinc ion battery with a sandwich structure. Since the electrode and the gel electrolyte can be stretched more than 100%, the flexible stretchable zinc ion battery can also be stretched 100%. Since the electrode can be prepared in a large area, the flexible zinc ion battery can also be prepared in a large area. The flexible zinc-air battery has good bending, curling, twisting and deformation capabilities and can be stretched 100%. The flexible stretchable zinc ion battery maintains stable charging and discharging performance after stretching and deformation, and has good application prospects in the field of wearable devices. The preparation method of the present invention is simple, low-cost, and can prepare stretchable electrode materials in large quantities. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a schematic diagram of the preparation of the spandex fabric-based anode of the present application;

[0050] Figure 2 Schematic diagram of the preparation of the spandex fabric-based cathode of the present application (wherein, Figure 2 a is a schematic diagram of the preparation of spandex fabric-based single-walled carbon tube cathode current collector; Figure 2 b is a schematic diagram of the preparation of a spandex fabric-based cathode that solidifies active substances by dynamic stretching and ultraviolet irradiation);

[0051] Figure 3 This is a schematic diagram of a flexible and stretchable zinc-ion battery with basic characteristics of spandex fabric of the present application;

[0052] Figure 4 is a photograph of the basic characteristics of the spandex fabric prepared in Example 1 of the present application, which is a flexible and stretchable zinc ion battery anode and cathode (wherein, Figure 4 a is a photo of the battery anode; Figure 4 b is a photo of the battery cathode);

[0053] Figure 5 This is a stretching display diagram of the basic characteristics of the spandex fabric prepared in Example 1 of the present application, which is a flexible and stretchable zinc ion battery (wherein, Figure 5 a is a photo of the zinc ion battery without stretching; Figure 5 b is a photo of a zinc ion battery stretched 50%; Figure 5 c is a photo of a zinc ion battery stretched 100%);

[0054] Figure 6 This is a cycle performance diagram of a flexible stretchable zinc ion battery based on the basic characteristics of the spandex fabric prepared in Example 1 of the present application (wherein, Figure 6 a is the CV curve of zinc ion battery under different stretching changes; Figure 6 b shows the current density of zinc ion battery at 0.5 A g under tensile strain of 0, 25%, 50%, 75% and 100%. -1 Cycle performance; Figure 6 c is the basic characteristics of spandex fabric. The current density of the flexible stretchable zinc-ion battery is 0.5 A g after being stretched 100%. -1 cycle performance). DETAILED DESCRIPTION

[0055] The invention will be further described below with reference to the accompanying drawings and embodiments.

[0056] Example 1

[0057] A method for preparing a flexible and stretchable zinc ion battery based on spandex fabric, comprising the following steps:

[0058] (1) Preparation of galvanized anode of spandex fabric (such as Figure 1shown):

[0059] 1.1 Place the spandex fabric in an air plasma cleaner for 5 minutes for surface modification, then soak the treated fabric in a degreasing solution (purchased from Shenzhen Zirconium Vanadium Technology Co., Ltd.) for 30 minutes and wash with water.

[0060] 1.2 Pre-stretch the washed fabric to 120% and place it in 50Mm SnCl 2 The fabric was immersed in 3 mM PdCl 2 Vacuum soak in the solution for 30 minutes to activate the surface.

[0061] 1.3 The surface activated fabric was placed in a chemical copper plating solution (purchased from Shenzhen Zirconium Vanadium Technology Co., Ltd.) and soaked at 35°C for 4 hours. After being taken out, it was washed with water several times and placed in a vacuum drying oven at 60°C for 2 hours to obtain a spandex fabric copper-plated sample.

[0062] 1.4 The copper-plated spandex fabric sample was used as the working electrode and the zinc plate as the counter electrode. The zinc anode was prepared by dynamic stretching. Under a constant voltage of -1 V, the zinc anode was heated to 250 g L -1 ZnSO 4 , 5g L -1 Al 2 (SO 4 ) 3 and 30g L -1 Na 2 SO 4 The zinc-plated anode of spandex fabric was prepared by electroplating in aqueous solution for 10-15 minutes.

[0063] (2) Preparation of spandex fabric active material cathode:

[0064] 2.1 4.15 g of aqueous carbon nanotube dispersion and 0.85 g of aqueous graphene dispersion were mixed into 10 g of water, and methylenebisacrylamide (0.002 g) and ammonium persulfate (0.02 g) initiators were added, and the dispersion was uniformly dispersed by ultrasonication. Subsequently, 0.5 g of MnO 2 Add to the above solution, sonicate again for 10 minutes, add 0.25 g of sodium carboxymethyl cellulose, and stir thoroughly until a paste consistency. Finally, add 1 g of acrylamide (AM) to the resulting solution and stir for 2 hours to prepare an active material ink.

[0065] 2.2 Use deionized water to prepare a 0.1g / L surfactant sodium dodecyl sulfate (SDS) solution, then add 50mg of single-walled carbon nanotube powder to the solution, put the above solution into an ultrasonic cell crusher, and obtain a stably dispersed carbon nanotube suspension after ultrasonic oscillation. The power of the ultrasonic cell crusher is 600W, and the ultrasonic time is 30min. Take a piece of fabric that has been treated with an air plasma cleaner and degreased and dried, pre-stretch it to 120%, put the carbon nanotube suspension into a spray gun and spray it on the fabric, then release the stretch and put the fabric into a 60°C oven to dry for 2h, wash the dried fabric several times with water, and then dry it. Then repeat the above steps on the other side of the fabric to obtain a single-walled carbon tube spandex fabric sample (such as Figure 2 a).

[0066] 2.3 The single-walled carbon tube spandex fabric was stretched to 100%, and the prepared manganese dioxide ink was evenly coated on the fabric current collector by a doctor blade method, and then the stretching was immediately released. The fabric was exposed to ultraviolet light for 20 minutes (ultraviolet wavelength 365nm, power 5W) by a dynamic stretching method to solidify the manganese dioxide ink on the single-walled carbon tube spandex fabric, and the spandex fabric active material cathode (such as Figure 2 b).

[0067] (3) Preparation of solid electrolyte - polyvinyl alcohol (PVA) hydrogel:

[0068] 2 mol / L ZnCl 2 and 0.2 mol / L MnCl 2 Dissolve in acidic water (18 mL) to prepare a gel electrolyte. Then add 1 g of ethylene glycol and 1 g of graphene oxide dispersion to disperse the solution evenly, then disperse and add 4 g of PVA to fully swell the PVA, then stir the solution in a water bath at 95 ° C for 2 h, then pour the gel precursor into a mold and freeze-dry overnight to obtain PVA / ZnCl 2 / MnCl 2 Hydrogel films.

[0069] (4) Preparation of flexible and stretchable zinc-ion batteries with sandwich structure:

[0070] The Ecoflex-0050 precursor solution was poured into a 1 mm deep glass mold and cured at 60°C for 1 h to prepare an elastic silicone rubber film. Then, the spandex fabric galvanized anode prepared in step (1) and the spandex fabric active material cathode prepared in step (2) were attached to the Ecoflex film using the Ecoflex precursor as glue and cured at 60°C for 30 min. Then, the liquid PVA / ZnCl prepared in step (3) was 2 / MnCl 2The gel precursor was coated on the zinc-coated fabric and the manganese dioxide-coated fabric, and then the zinc-coated fabric and the manganese dioxide-coated fabric were placed on the PVA / ZnCl 2 / MnCl 2 The two sides of the hydrogel film form a flexible and stretchable zinc-ion battery. Finally, the Ecoflex precursor is poured on the edge of the battery and solidified to obtain a flexible and stretchable zinc-ion battery with a sandwich structure (such as Figure 3 shown).

[0071] Since the prepared battery anode (such as Figure 4 a) and cathode (as Figure 4 b) is stretchable, so the spandex fabric prepared has the basic characteristics of flexible stretchable zinc ion battery. The physical display under the tensile strain of 0%, 50%, and 100% is shown as follows Figure 5 a. Figure 5 b. Figure 5 c. The CV curves of the battery under tensile strains of 0, 25%, 50%, 75%, and 100% are shown in Figure 6 a, the charge and discharge cycle curve is shown in Figure 6 As shown in b, the curve shape and value of the result are similar, which indicates that the discharge specific capacity is similar at the same current density. The capacity retention rate of the flexible stretchable zinc-ion battery after 260 cycles of stretching 100% is above 68% (as shown in Figure 6 c), indicating that the basic characteristics of spandex fabric are flexible and stretchable. The battery performance of zinc-ion battery remains stable under different tensile strains.

[0072] Example 2

[0073] A method for preparing a flexible and stretchable zinc ion battery based on spandex fabric, comprising the following steps:

[0074] (1) Preparation of spandex fabric galvanized anode:

[0075] 1.1 Place the spandex fabric in an air plasma cleaner for 5 minutes for surface modification, then soak the treated fabric in a degreasing solution (purchased from Shenzhen Zirconium Vanadium Technology Co., Ltd.) for 30 minutes and wash with water.

[0076] 1.2 Pre-stretch the washed fabric to 120% and place it in 50Mm SnCl 2 The fabric was immersed in 3 mM PdCl 2 Vacuum soak in the solution for 30 minutes to activate the surface.

[0077] 1.3 The surface activated fabric was placed in a chemical copper plating solution (purchased from Shenzhen Zirconium Vanadium Technology Co., Ltd.) and soaked at 35°C for 4 hours. After being taken out, it was washed with water several times and placed in a vacuum drying oven at 60°C for 2 hours to obtain a spandex fabric copper-plated sample.

[0078] 1.4 The copper-plated spandex fabric sample was used as the working electrode and the zinc plate as the counter electrode. The zinc anode was prepared by dynamic stretching. Under a constant voltage of -1 V, the zinc anode was heated to 250 g L -1 ZnSO 4 , 5g L -1 Al 2 (SO 4 ) 3 and 30g L -1 Na 2 SO 4 The spandex fabric was electroplated in aqueous solution for 10-15 minutes to form a zinc anode.

[0079] (2) Preparation of spandex fabric active material cathode:

[0080] 2.1 4.15 g of aqueous carbon nanotube dispersion and 0.85 g of aqueous graphene dispersion were mixed into 10 g of water, and methylenebisacrylamide (0.002 g) and ammonium persulfate (0.02 g) initiators were added, and the dispersion was uniformly dispersed by ultrasonication. Subsequently, 0.5 g of MnO 2 Add to the above solution, sonicate again for 10 minutes, add 0.25 g of sodium carboxymethyl cellulose, and stir thoroughly until a paste consistency. Finally, add 1 g of acrylamide (AM) to the resulting solution and stir for 2 hours to prepare an active material ink.

[0081] 2.2 Prepare a 0.1g / L surfactant sodium dodecyl sulfate (SDS) solution with deionized water, then add 50mg of single-walled carbon nanotube powder to the solution, put the above solution into an ultrasonic cell crusher, and obtain a stably dispersed carbon nanotube suspension after ultrasonic oscillation. The power of the ultrasonic cell crusher is 600W, and the ultrasonic time is 30min. Take a piece of fabric treated by an air plasma cleaner and degreased and dried, pre-stretch it to 120%, put the carbon nanotube suspension into the spray gun and spray it on the fabric, then release the stretch and put the fabric into a 60°C oven to dry for 2h, wash the dried fabric several times, and then dry it. Then repeat the above steps on the other side of the fabric to obtain a single-walled carbon tube spandex fabric sample.

[0082] 2.3 The single-walled carbon tube spandex fabric was stretched to 100%, and the prepared manganese dioxide ink was evenly coated on the fabric current collector by a doctor blade method, and then the stretching was immediately released. The fabric was exposed to ultraviolet light for 20 minutes (ultraviolet wavelength 365nm, power 5W) by a dynamic stretching method to solidify the manganese dioxide ink on the single-walled carbon tube spandex fabric, and the spandex fabric active material cathode was prepared.

[0083] (3) Preparation of solid electrolyte - acrylamide (PAM) hydrogel:

[0084] 2 mol / L ZnSO 4 and 0.2 mol / L MnSO 4 Dissolve in 20 mL of deionized water, add 4 g of acrylamide and stir to dissolve, then add 2.4 mg of methylenebisacrylamide, 24 mg of ammonium persulfate and 28 mg of tetramethylethylenediamine respectively, stir to dissolve evenly, then pour the gel precursor into the mold and polymerize at 60 ° C for 45 minutes to obtain PAM / ZnSO 4 / MnSO 4 Hydrogel films.

[0085] (4) Preparation of flexible and stretchable zinc-ion batteries with sandwich structure:

[0086] The Ecoflex-0050 precursor solution was poured into a 1 mm deep glass mold and cured at 60°C for 1 h to prepare an elastic silicone rubber film. Then, the spandex fabric galvanized anode prepared in step (1) and the spandex fabric active material cathode prepared in step (2) were attached to the Ecoflex film using the Ecoflex precursor as glue and cured at 60°C for 30 min. Then, the liquid PVA / ZnSO prepared in step (3) was 4 / MnSO 4 The gel precursor was coated on the zinc-coated fabric and the manganese dioxide-coated fabric, and then the zinc-coated fabric and the manganese dioxide-coated fabric were placed on the PVA / ZnSO 4 / MnSO 4 The two sides of the hydrogel film form a flexible and stretchable zinc-ion battery. Finally, the Ecoflex precursor is poured on the edge of the battery and solidified to obtain a flexible and stretchable zinc-ion battery with a sandwich structure. The assembled battery has stable performance and little change when stretched.

[0087] Example 3

[0088] A method for preparing a flexible and stretchable zinc ion battery based on spandex fabric, comprising the following steps:

[0089] (1) Preparation of spandex fabric galvanized anode: The preparation steps are the same as those in Example 1.

[0090] (2) Preparation of spandex fabric active material cathode: the preparation steps are the same as those in Example 1.

[0091] (3) Preparation of solid electrolyte - polyvinyl alcohol (PVA) hydrogel:

[0092] 2 mol / L ZnCl 2 and 0.2 mol / L MnCl 2 Dissolve in acidic water (18 mL) to prepare a gel electrolyte. Then add 1 g of ethylene glycol and 1 g of graphene oxide dispersion to disperse the solution evenly, then disperse and add 4 g of PVA to fully swell the PVA, then stir the solution in a water bath at 95 ° C for 2 h, then place the treated spandex fabric in a mold, cast the gel precursor evenly on the spandex fabric, and freeze-dry overnight to obtain spandex fabric-based PVA / ZnCl 2 / MnCl 2 Hydrogel films.

[0093] (4) Preparation of flexible and stretchable zinc-ion batteries with sandwich structure:

[0094] The Ecoflex-0050 precursor solution was poured into a 1 mm deep glass mold, and the treated spandex fabric was immersed in the Ecoflex-0050 precursor solution and cured at 60°C for 1 hour to prepare a spandex fabric-based elastic silicone rubber film. Then, the spandex fabric galvanized anode prepared in step (1) and the spandex fabric active material cathode prepared in step (2) were attached to the spandex fabric-based Ecoflex film using the Ecoflex precursor as glue and cured at 60°C for 30 minutes. Then, the liquid PVA / ZnCl prepared in step (3) was 2 / MnCl 2 The gel precursor was coated on the zinc-coated fabric and the manganese dioxide-coated fabric, and then the zinc-coated fabric and the manganese dioxide-coated fabric were placed on the spandex fabric-based PVA / ZnCl 2 / MnCl 2 The two sides of the hydrogel film form a flexible and stretchable zinc-ion battery. Finally, the Ecoflex precursor is poured on the edge of the battery and solidified to obtain a flexible and stretchable zinc-ion battery with a sandwich structure.

[0095] Example 4

[0096] A method for preparing a flexible and stretchable zinc ion battery based on spandex fabric, comprising the following steps:

[0097] (1) Preparation of spandex fabric galvanized anode: The preparation steps are the same as those in Example 1.

[0098] (2) Preparation of spandex fabric active material cathode: the preparation steps are the same as those in Example 1.

[0099] (3) Preparation of solid electrolyte - acrylamide (PAM) hydrogel:

[0100] 2 mol / L ZnSO 4 and 0.2 mol / L MnSO 4 Dissolve in 20 mL of deionized water, add 4 g of acrylamide and stir to dissolve, then add 2.4 mg of methylenebisacrylamide, 24 mg of ammonium persulfate and 28 mg of tetramethylethylenediamine respectively, stir to dissolve evenly, then place the treated spandex fabric in a mold, cast the gel precursor evenly on the spandex fabric, polymerize at 60 ° C for 45 minutes, and obtain spandex fabric-based PAM / ZnSO 4 / MnSO 4 Hydrogel films.

[0101] (4) Preparation of flexible and stretchable zinc-ion batteries with sandwich structure:

[0102] The Ecoflex-0050 precursor solution was poured into a 1 mm deep glass mold, and the treated spandex fabric was immersed in the Ecoflex-0050 precursor solution and cured at 60°C for 1 h to prepare a spandex fabric-based elastic silicone rubber film. Then, the spandex fabric galvanized anode prepared in step (1) and the spandex fabric active material cathode prepared in step (2) were attached to the spandex fabric-based Ecoflex film using the Ecoflex precursor as glue and cured at 60°C for 30 min. Then, the liquid PAM / ZnSO prepared in step (3) was 4 / MnSO 4 The gel precursor was coated on the zinc-coated fabric and the manganese dioxide-coated fabric, and then the zinc-coated fabric and the manganese dioxide-coated fabric were placed on the spandex fabric-based PAM / ZnSO 4 / MnSO 4 The two sides of the hydrogel film form a flexible and stretchable zinc-ion battery. Finally, the Ecoflex precursor is poured on the edge of the battery and solidified to obtain a flexible and stretchable zinc-ion battery with a sandwich structure.

[0103] The present invention selects spandex fabric as a substrate, and prepares a stretchable battery anode and cathode by a method of dynamic stretching electrogalvanizing and dynamic stretching ultraviolet irradiation coagulation of active substances, thereby ensuring the stretchability of the electrode. The electrolyte adopts an in-situ cross-linking method so that the electrolyte can be filled into the interior of the spandex fabric electrode, thereby increasing the contact area between the electrode and the electrolyte. Therefore, the assembled flexible stretchable zinc ion battery has a higher specific capacity and energy density, as well as better cycle stability. Benefiting from the fact that each component of the battery can be stretched by more than 100%, the flexible stretchable zinc ion battery of the present invention can be stretched by 100%, and the charge and discharge performance is stable under different stretching conditions.

[0104] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A flexible and stretchable zinc ion battery based on spandex fabric, characterized in that: It includes a stretchable electrode and a stretchable gel electrolyte film; the stretchable electrode includes a spandex fabric-based anode and a spandex fabric-based cathode, and the stretchable gel electrolyte film is arranged between the spandex fabric-based anode and the spandex fabric-based cathode; The spandex fabric-based anode is a spandex fabric-based galvanized electrode, the spandex fabric-based galvanized electrode comprises a copper-plated layer and a galvanized layer arranged outside the copper-plated layer, and the copper-plated layer is a copper-plated fabric; The spandex fabric-based cathode is a spandex fabric-based active substance ink electrode, which includes a single-walled carbon nanotube layer and an active substance ink layer outside the single-walled carbon nanotube layer; the single-walled carbon nanotube layer is a fabric sprayed with a single-walled carbon nanotube dispersion, and the active substance ink layer is a dynamically stretched ultraviolet irradiation solidified active substance ink. The stretchable electrolyte film is selected from one or more of polyvinyl alcohol hydrogel, polyacrylamide hydrogel, spandex fabric-based polyvinyl alcohol hydrogel, and spandex fabric-based polyacrylamide hydrogel.

2. The flexible stretchable zinc ion battery based on spandex fabric according to claim 1, characterized in that: The preparation method of the copper plating layer comprises the following steps: A1. Cut the spandex fabric into small pieces and perform surface modification treatment; A2, the treated spandex fabric is immersed in the degreasing solution for 10-60 minutes, the spandex fabric is pre-stretched by 120% after washing, and the fabric is vacuum immersed in SnCl2 hydrochloric acid solution for 10-60 minutes, and then taken out and vacuum immersed in PdCl2 hydrochloric acid solution for 10-60 minutes to obtain a surface activated spandex fabric; A3. Soaking the surface activated spandex fabric in a chemical copper plating solution to deposit metallic copper on the surface to form a copper plating layer, thereby obtaining a copper-plated fabric.

3. A flexible stretchable zinc ion battery based on spandex fabric according to claim 2, characterized in that: In step A2, the concentration of the SnCl2 hydrochloric acid solution is 30-100 mM, and the concentration of the PdCl2 hydrochloric acid solution is 1-5 mM; in step A3, the immersion temperature is 30-40°C and the immersion time is 2-8 h.

4. The flexible stretchable zinc ion battery based on spandex fabric according to claim 1, characterized in that: The preparation method of the spandex fabric-based galvanized electrode comprises the following steps: adopting a dynamic stretching method, using a copper-plated layer as a cathode and a zinc plate as an anode to form a two-electrode electroplating system, electroplating for 10-20 minutes at a voltage of -0.5V to -2V to form a zinc-plated layer, and obtaining a spandex fabric-based galvanized electrode; during the dynamic stretching process, the copper-plated fabric can continuously maintain a stretching and recovery cycle, with each cycle being 1.5-2.5s.

5. The flexible stretchable zinc ion battery based on spandex fabric according to claim 1, characterized in that: The method for preparing a single-walled carbon nanotube layer comprises the following steps: B1. Prepare a surfactant sodium dodecyl sulfate solution with deionized water, and then add the single-walled carbon nanotube powder into the solution; B2, subjecting the above solution to ultrasonic oscillation treatment to obtain a stably dispersed carbon nanotube suspension; B3. Take the dry spandex fabric after surface modification and degreasing, pre-stretch it to 120%, spray the carbon nanotube suspension on both sides of the fabric, then release the stretch and dry the fabric, wash the dried fabric several times and dry it to obtain a single-walled carbon nanotube layer.

6. The flexible stretchable zinc ion battery based on spandex fabric according to claim 5, characterized in that: In step B1, the concentration of the sodium dodecyl sulfate solution is 0.1-0.15 g / L; in step B2, the power of the ultrasonic oscillation treatment is 500-700 W, the ultrasonic time is 30-50 minutes, and the concentration of the obtained carbon nanotube suspension is 0.05-0.1 g / L.

7. The flexible stretchable zinc ion battery based on spandex fabric according to claim 1, characterized in that: The method for preparing active material ink comprises the following steps: C1, mixing an aqueous carbon nanotube dispersion and an aqueous graphene dispersion into water, adding methylenebisacrylamide and ammonium persulfate initiator, and performing ultrasonic treatment to make the dispersion uniform; C2. Add the active substance to the above solution, sonicate again, add sodium carboxymethyl cellulose, and stir thoroughly until completely dissolved; C3. Add acrylamide to the obtained solution, stir, and prepare active material ink.

8. The flexible stretchable zinc ion battery based on spandex fabric according to claim 7, characterized in that: In step C1, the mass ratio of the aqueous carbon nanotube dispersion to the aqueous graphene dispersion is (0.8-0.9):0.17; in step C2, the active substance is selected from metal oxides, the metal oxides include MnO2, V2O5, Fe3O4, the mass ratio of the active substance to the aqueous graphene dispersion is (0.4-0.6):0.85, and the mass ratio of sodium carboxymethyl cellulose to the aqueous graphene dispersion is (0.03-0.05):0.17; in step C3, the mass ratio of acrylamide to the aqueous graphene dispersion is (0.1-0.3):0.

17.

9. The flexible stretchable zinc ion battery based on spandex fabric according to claim 1, characterized in that: The preparation method of spandex fabric-based active substance ink electrode comprises the following steps: stretching the fabric sprayed with single-walled carbon nanotube dispersion to 100%, uniformly coating the active substance ink on the fabric current collector by a scraper method, and then immediately releasing the stretching; exposing the fabric to ultraviolet light for 20-30 minutes by a dynamic stretching method to solidify the active substance ink on the single-walled carbon nanotube coated fabric, thereby obtaining a spandex fabric-based active substance ink electrode.

10. A method for preparing a flexible and stretchable zinc ion battery based on the spandex fabric according to any one of claims 1 to 9, characterized in that: The following steps are involved: D1. Paste the spandex fabric-based galvanized electrode on the elastic rubber film or the spandex fabric-based elastic silicone rubber film, and then cure it to obtain a bonded spandex fabric-based galvanized anode-rubber film; D2, pasting the spandex fabric-based active substance ink electrode on the elastic rubber film or the spandex fabric-based elastic silicone rubber film, and then curing it to obtain a well-bonded spandex fabric-based active substance ink cathode-rubber film; D3. Coat the liquid gel precursor of the stretchable electrolyte film on the spandex fabric-based galvanized anode and the spandex fabric-based active material ink cathode, then stack and assemble the spandex fabric-based galvanized anode and the spandex fabric-based active material ink cathode, and set the stretchable electrolyte film between the two electrodes, and then cure and seal the edges to form a flexible stretchable zinc ion battery with a sandwich structure.